COORDINATION OF NATIONAL ACCOUNTING WITH INTERNATIONAL STANDARDS IN THE REPUBLIC OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article discusses the procedure for adjusting the accounting in the organizations of the Republic of Uzbekistan in the context of the transition to the use of international financial reporting standards. It was emphasized that the purpose of the accounting reform is to bring the national accounting system in line with international financial reporting standards and the requirements of a market economy. The article discusses the real benefits of the introduction of IFRS, as well as the real challenges faced by enterprises, audit companies, educational institutions that provide basic professional accounting training in the transition to international standards. The need to develop a conversion methodology and define a list of enterprises that are needed and should be applied to international investment programs and access to foreign markets.